EVALUATION OF ASSORTMENTS CONSIDERING DIFFERENT STUMP AND PRE-BUCKING DISC HEIGHTS IN MECHANIZED HARVESTING OPERATIONS OF A Pinus taeda L. FOREST - Silva Oliveira, Gustavo; Casemiro Soares, Philipe Ricardo; Sampietro, Jean Alberto; Saturnino da Silva, Maycon Thuan; Nicoletti, Marcos Filipe; Peretti da Silva., Julio (Floresta, 2019)
This study aimed to evaluate assortments by adopting distinct stump heights and pre-bucking disc heights in the mechanized harvesting operations of a Pinus taeda L. forest, which is owned by a company located in Campo Belo do Sul (SC). To that end, the simulation of six scenarios was carried out after the forest’s clear-cutting. The scenario 1 includes the company’s specifications. Scenario 2 includes the real situation, that is, the measurements made in sample units installed on the field and scenario 3 includes stump heights of 10 cm and pre-bucking disc heights of 5 cm. In the other scenarios, stump and pre-bucking disc heights with values higher than the ones specified by the company were included. Then, using a taper function, we calculated the assortments in tons per hectare (t ha-1) and monetary value per hectare (R ha-1), considering the price of wood with bark (R t-1) for each assortment. Results show that Scenario 1 presented a larger amount of wood, however, Scenario 3 represented higher revenue due to the higher wood quantity of the value-added assortments. On the other hand, Scenario 6 presented the lowest amount of wood comparing to the others, and Scenario 2 presented the lowest economic return. All things considered, the company performs its activities below what is planned, but with production higher than the other evaluated scenarios. Regarding the economic return, the other scenarios are more feasible than Scenario 2, which shows that the company needs to seek process improvements with the implementation of another scenario that could bring better results.